Carbon-based material aqueous dispersion and application thereof

By designing multi-block copolymer dispersants with hydrophobic and hydrophilic monomers, the agglomeration problem of carbon-based materials during stirring was solved, achieving stable and efficient dispersion of carbon-based materials in water and reducing process costs.

CN120924183APending Publication Date: 2025-11-11ZHEJIANG LANTIAN ENVIRONMENTAL PROTECTION HI TECH CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410575547.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Carbon-based materials are prone to agglomeration during stirring, and existing dispersants suffer from poor dispersion or high processing costs.

Method used

Multi-block copolymers are designed using hydrophobic and hydrophilic monomer dispersants to form multi-block copolymer dispersants. These dispersants form a stable hydration layer on the surface of carbon-based materials through strong and weak adsorption, thereby achieving effective dispersion.

Benefits of technology

Stable dispersion of carbon-based materials in water was achieved, improving the stability and dispersion performance of the dispersion and reducing process costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120924183A_ABST
    Figure CN120924183A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-based material aqueous dispersion, which comprises a carbon-based material and a dispersant, the dispersant is a multi-block copolymer represented by formula (1), a hydrophobic chain segment of the dispersant can form multi-point strong adsorption with the surface of the carbon-based material, and at the same time, an amphiphilic PEG side chain has weak adsorption with the surface of the carbon-based material. According to the mode of combining strong adsorption and weak adsorption, a hydration layer can be formed on the surface of the carbon-based material, the effect of stabilizing an interface is achieved, the carbon-based material is stably dispersed into water, and the problem that the carbon-based material is agglomerated in the stirring process is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aqueous dispersion of carbon-based materials, and more specifically to an aqueous dispersion of carbon-based materials and its applications. Background Technology

[0002] With the continuous development of rechargeable battery technology, people have increasingly higher requirements for the performance of rechargeable batteries, such as cycle life, storage, and internal resistance. Among these, the dispersion of conductive agents in electrode materials has a significant impact on battery performance; poor dispersion of conductive agents in electrode materials will affect battery performance.

[0003] Conductive agents are prone to agglomeration during the preparation of battery electrodes, making uniform dispersion difficult. Existing technologies mainly disclose two methods for dispersing conductive agents. The first method alleviates the agglomeration problem by incorporating dispersants. For example, patent document CN107528067A uses resins containing polycyclic aromatic hydrocarbon groups or polyvinyl alcohol resins as dispersing resins; patent document CN115621463A uses polyvinylpyrrolidone and sodium carboxymethyl cellulose as dispersants; and patent document CN111916743A uses sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl phosphate, and hexadecyltrimethyl bromide. Ammonium, sodium polyacrylate, and sodium lignosulfonate are used as dispersants; patent document CN115340624A uses polymers with carboxylic acid groups as side chains as dispersants. The second approach is to modify conductive agents to improve agglomeration problems. For example, patent document WO2023044754A1 discloses a conductive binder that polymerizes VDF by selecting a chain transfer agent with a specific structure. This binder can be used to perform surface grafting modification on carbon-based conductive agent particles, thereby improving the problem of easy agglomeration of carbon-based conductive agents during slurry stirring.

[0004] The first method, involving the incorporation of dispersants, suffers from issues such as unsatisfactory dispersion effects and side reactions between the dispersant and materials used in the battery. Further research is needed on the specific types of dispersants required. The second method, surface grafting modification of conductive agents, has high processing costs, making it unsuitable for practical applications. Summary of the Invention

[0005] The technical problem that the invention aims to solve

[0006] This invention addresses the problem of carbon-based material agglomeration. Its purpose is to solve the problem of carbon-based materials agglomerating during stirring and to provide an aqueous dispersion of carbon-based materials.

[0007] Technical solutions for solving the problem

[0008] To solve the above-mentioned technical problems, the inventors discovered that a dispersant with hydrophobic and hydrophilic monomers can effectively disperse conductive agents, with a particle size of 200–5000 nm after dispersion.

[0009] In a first aspect, the present invention provides an aqueous dispersion of a carbon-based material, comprising a carbon-based material and a dispersant, wherein the dispersant is a multi-block copolymer of formula (1).

[0010]

[0011] Among them, R 1 R 4 It is independently selected from hydrogen, C1-C5 straight-chain or branched alkyl, or C1-C5 straight-chain or branched alkyl ether;

[0012] R 2 R 5 Independently selected from oxygen, imino, C1-C9 straight-chain or branched or cyclic alkyl imino, C1-C9 aryl imino;

[0013] R 3 Selected from phenyl, C1-C4 straight-chain or branched alkyl groups;

[0014] R 6 Selected from polyethylene glycol derivatives (CH2CH2O) q Z, where q is an integer greater than 9 and less than or equal to 100, and Z is selected from hydrogen, C1-C3 straight-chain or branched alkyl groups.

[0015] The dispersant of this invention has the following characteristics: 1) The dispersant is a multi-block copolymer, in which the multi-block hydrophobic segments ensure strong adsorption of the dispersant molecules at multiple points on the surface of carbon-based materials; 2) The amphiphilic PEG side chains of the dispersant have weak adsorption forces with the surface of carbon-based materials and form a hydration layer, stabilizing the interface; 3) The main chain conformation of the dispersant spontaneously reconstructs after adsorption onto the surface of carbon-based materials, forming a matching hydration layer with the surface of the carbon-based materials. The dispersant of this invention can match various carbon-based materials and form an adsorption layer on their surface, and stably disperse the carbon-based materials in water through the hydration layer.

[0016] To improve interfacial wettability, increase steric hindrance of the surface hydration layer, and enhance dispersion stability, R is preferably preferred. 1 R 4 Independently selected from hydrogen and methyl; R 2 R 5 Independently selected from oxygen and imino groups; R 3 Selected from phenyl, C1-C4 straight-chain or branched alkyl groups; R 6 Selected from polyethylene glycol derivatives (CH2CH2O) qZ, where q is an integer greater than 9 and less than or equal to 100, and Z is selected from hydrogen, C1-C3 straight-chain or branched alkyl groups. More preferably, R 1 R 4 Independently selected from methyl; R 2 R 5 Independently selected from oxygen; R 3 Selected from phenyl, methyl, tert-butyl; R 6 Selected from polyethylene glycol derivatives (CH2CH2O) q Z, where q is an integer greater than 9 and less than or equal to 50, and Z is selected from hydrogen, C1-C3 straight-chain or branched alkyl groups.

[0017] The dispersant of this invention increases kinetic dispersion stability through steric hindrance. The length of the polyethylene glycol segment on the side chain of the dispersant is a key factor. When R 6 When the degree of polymerization (q value) of polyethylene glycol is too low, the steric hindrance of the polyethylene glycol chain segments results in a large particle size and poor dispersibility in the aqueous dispersion of carbon-based materials. When R 6 When the degree of polymerization (q value) of polyethylene glycol is greater than 4, especially greater than 9, polyethylene glycol can form a highly sterically hindered hydration layer, allowing the dispersant to form a stable monomolecular micelle structure in water. This results in smaller micelle particle sizes and better dispersion performance. Preferably, R 6 The degree of polymerization (q value) of polyethylene glycol is greater than 20. R 6 The degree of polymerization (q value) of the polyethylene glycol is less than or equal to 100, preferably less than or equal to 50.

[0018] In some embodiments, the dispersant is a multiblock copolymer with more than 5 blocks, and the block length of a single block is 1 to 10.

[0019] In some embodiments, the dispersant satisfies at least one of conditions (I) to (III):

[0020] (I)x+y=1, and x / y=1~9,

[0021] (II) The HLB value of the dispersant is 8 to 14.

[0022] (III) The micelles formed by the dispersant in water have a micelle size of 5 to 30 nm.

[0023] To improve interfacial wettability, increase the steric hindrance of the surface hydration layer, and enhance dispersion performance, preferably, x + y = 1, and x / y = 2–6. Considering factors such as improving interfacial wettability, increasing the steric hindrance of the surface hydration layer, and enhancing dispersion stability, preferably, the HLB value is 10–12. Preferably, the micelle size formed by the dispersant in water is 7–15 nm.

[0024] In some embodiments, the number-average molecular weight of the dispersant is 5,000 to 100,000; preferably, it is 10,000 to 60,000. When the molecular weight is below the lower limit, stable monomolecular micelles cannot be formed, and the structure of a multiblock copolymer cannot be satisfied. When the molecular weight is above the upper limit, the average particle size is too high, and the mobility of molecular chain segments decreases, resulting in reduced dispersion performance.

[0025] In some embodiments, the specific surface area of ​​the carbon-based material is 10–1000 m². 2 / g, wherein the carbon-based material is selected from at least one of superconducting carbon, carbon black SP, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, superconducting celestial black, graphite, artificial graphite, carbon, carbon black, activated carbon, acetylene black, phenolic resin, asphalt, tar, and carbon fiber.

[0026] In some embodiments, the average particle size of the aqueous dispersion of the carbon-based material is 200–5000 nm.

[0027] In some embodiments, the carbon-based material is carbon black SP, and the average particle size of the aqueous dispersion of the carbon-based material is 400–3000 nm.

[0028] In some embodiments, the dispersant accounts for 5% to 10% of the total mass of the aqueous dispersion of the carbon-based material.

[0029] In some embodiments, the aqueous dispersion of the carbon-based material comprises one or more additives selected from the group consisting of: defoamers, thickeners, rheology modifiers, and wetting agents.

[0030] The defoamer is a commonly used defoamer in the art. Preferably, the defoamer is selected from polyethylene glycol-polypropylene glycol copolymer, silane, etc. In order to cooperate with the dispersant to achieve a synergistic dispersion effect, more preferably, the defoamer is selected from triblock polyethylene glycol-polypropylene glycol copolymer.

[0031] The thickener is a commonly used thickener in the art. In order to work synergistically with the dispersant to achieve a dispersing effect, the thickener is preferably selected from polypyrrolidone.

[0032] The wetting agent is a commonly used wetting agent in the art. Preferably, the wetting agent is selected from polyethylene glycol-polypropylene glycol copolymer in order to achieve a synergistic dispersion effect with the dispersant. More preferably, the wetting agent is selected from random polyethylene glycol-polypropylene glycol copolymer.

[0033] Secondly, the present invention provides a method for preparing an aqueous dispersion of a carbon-based material, the method comprising the following steps:

[0034] (1) In a mixing device, an aqueous solution of dispersant, a carbon-based material and water are added;

[0035] (2) After grinding and filtration, an aqueous dispersion of carbon-based materials is obtained.

[0036] Thirdly, the present invention provides an application of an aqueous dispersion of a carbon-based material, wherein the aqueous dispersion of the carbon-based material is used as a conductive agent in the preparation of a PVDF conductive binder.

[0037] The method for preparing the dispersant of the present invention includes the step of polymerizing at least one compound represented by formula (2) and formula (3) in a solvent.

[0038]

[0039] R 1 R 2 R 3 R 4 R 5 R 6 Same as the description in the first aspect.

[0040] The dispersant is a random copolymer, and the polymerization ratio of the monomers shown in formula (2) and formula (3) is 0.5 to 2.5, which enables the monomer units shown in formula (2) and formula (3) to be dispersed on the main chain of the dispersant, resulting in better dispersion performance.

[0041] The comonomer of the structural unit shown in formula (2) can be selected from at least one of methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, phenyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, and phenyl methacrylate. From the perspective of dispersion performance and stability, preferably, it is selected from at least one of methyl methacrylate, propyl methacrylate, tert-butyl methacrylate, and phenyl methacrylate.

[0042] The molecular weight of the comonomer of the structural unit shown in formula (3) is 400 to 2000, and it is selected from at least one of polyethylene glycol methyl ether methacrylate, polyethylene glycol ethyl ether methacrylate, polyethylene glycol propyl ether methacrylate and polyethylene glycol methacrylate.

[0043] Compared with the prior art, the present invention has the following advantages: the hydrophobic segments of the dispersant provided by the present invention can form strong adsorption at multiple points on the surface of carbon-based materials, while the amphiphilic PEG side chains have weak adsorption on the surface of carbon-based materials. This combination of "strong adsorption-weak adsorption" can form a water splash layer on the surface of carbon-based materials, thereby stabilizing the interface and dispersing the carbon-based materials stably in water. Attached Figure Description

[0044] Figure 1 The average particle size distribution of the carbon black aqueous dispersion obtained in Example 1 is shown in the figure. Detailed Implementation

[0045] The present invention will be further described below with reference to specific embodiments, but the invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all alternatives, improvements, and equivalents that may be included within the scope of the claims.

[0046] This invention specifically discloses certain data ranges, suggesting that any lower limit can be combined with any upper limit to form an unspecified range, any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with other upper limits to form an unspecified range. Each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value, or with other lower or upper limits, to form an unspecified range.

[0047] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0048] Unless otherwise specified, all embodiments and preferred embodiments of the present invention can be combined with each other to form new technical solutions. Unless otherwise specified, all technical features and preferred technical features of the present invention can be combined with each other to form new technical solutions.

[0049] In this invention, Mn refers to the number-average molecular weight of the polymer; PDI refers to the polymer dispersibility index. The larger the PDI, the wider the molecular weight distribution; the smaller the PDI, the more uniform the molecular weight distribution.

[0050] R hThe hydrodynamic radius is used to measure the micelle size of the surfactant in the aqueous medium. The hydrodynamic radius is similar to that in isopropanol, indicating that the majority of micelles formed by the surfactant in the aqueous medium are monomolecular micelles. When the difference is significant, it indicates that the surfactant exhibits folding in the aqueous medium, resulting in a relatively low content of monomolecular micelles. The hydrodynamic radius was measured using a HORIBA / SZ-100Z2 instrument.

[0051] The test method of this invention:

[0052] Number average molecular weight (Mn) test: The number average molecular weight (Mn) was measured using a polystyrene gel permeation chromatography (GPC) column and standard PS polystyrene. The test sample was a 2 mg / ml dimethylformamide (DMF) solution, the pump flow rate was 1 ml / min, the mobile phase was DMF, the test temperature was 20℃, and the data acquisition frequency was 1 count / s.

[0053] Average particle size test: The instrument was a HORIBA / SZ100Z2 nanoparticle size analyzer, the test temperature was 25℃, the detector angle was 90°, and the test data was the z-average particle size.

[0054] Viscosity test: The instrument was a DV2T rotational viscometer, the test temperature was 30℃, and the test speed was 2.5 rpm.

[0055] All reagents used in this invention were purchased from Sigma-Aldrich.

[0056] Preparation Example

[0057] Preparation of dispersant A1 - methyl methacrylate, polyethylene glycol methyl ether methacrylate

[0058] Methyl methacrylate (4.0 g), polyethylene glycol methyl ether methacrylate (degree of polymerization 20, molecular weight approximately 950, 6.0 g), and isopropanol (5.0 g) were added to a three-necked flask purged with nitrogen. The mixture was stirred and heated to 80°C. After the temperature stabilized, dimethyl azobisisobutyrate (0.60 g) was added, and the mixture was heated and stirred for 15 hours until the monomer and initiator were completely converted (conversion rate greater than 99%). Pure water (85 g) was added and stirred until completely dissolved. The mixture was cooled and allowed to stand at room temperature to obtain a solution containing the surfactant. The surfactant had Mn = 64200, PDI = 1.89, formed micelles with a diameter of 11.6 nm in water, and a hydrodynamic radius R in isopropanol. h It is 16.3nm.

[0059] Preparation of dispersant A2 - methyl methacrylate, polyethylene glycol methyl ether methacrylate

[0060] Methyl methacrylate (2.5 g), polyethylene glycol methyl ether methacrylate (degree of polymerization 9, molecular weight approximately 475, 2.5 g), and isopropanol (5.0 g) were added to a three-necked flask purged with nitrogen. The mixture was stirred and heated to 90°C. After the temperature stabilized, dimethyl azobisisobutyrate (0.30 g) was added, and the mixture was heated and stirred for 8 hours until the monomer and initiator were completely converted (conversion rate greater than 99%). Pure water (85 g) was added and stirred until completely dissolved. After cooling and standing to room temperature, a solution containing the surfactant was obtained. The surfactant had Mn = 48300, PDI = 1.79, formed micelles with a diameter of 15.8 nm in water, and a hydrodynamic radius R in isopropanol. h It is 12.6nm.

[0061] Preparation of dispersant A3 - tert-butyl methacrylate, polyethylene glycol methyl ether methacrylate

[0062] 4.0 g of tert-butyl methacrylate, 6.0 g of polyethylene glycol methyl ether methacrylate (degree of polymerization 20, molecular weight approximately 950), and 5.0 g of isopropanol were added to a three-necked flask purged with nitrogen. The mixture was stirred and heated to 90 °C. After the temperature stabilized, 0.60 g of dimethyl azobisisobutyrate was added, and the mixture was heated and stirred for 8 hours until the monomer and initiator were completely converted (conversion rate greater than 99%). 85 g of pure water was added and stirred until completely dissolved. After cooling and standing to room temperature, a solution containing the surfactant was obtained. The surfactant had Mn = 53500, PDI = 1.93, formed micelles with a diameter of 13.3 nm in water, and a hydrodynamic radius R in isopropanol. h It is 13.8nm.

[0063] Preparation of Dispersant A4: 2.0 g of tert-butyl methacrylate, 3.0 g of polyethylene glycol methyl ether methacrylate (degree of polymerization 9, molecular weight approximately 475), and 5.0 g of isopropanol were added to a three-necked flask purged with nitrogen. The mixture was stirred and heated to 90°C. After the temperature stabilized, 0.30 g of dimethyl azobisisobutyrate was added. The mixture was heated and stirred for 8 hours until the monomer and initiator were completely converted (conversion rate greater than 99%). 85 g of pure water was added and stirred until completely dissolved. After cooling and standing to room temperature, a solution containing the surfactant was obtained. The surfactant Mn = 50400, PDI = 1.75, and the micelle size formed in water was 11.9 nm. The hydrodynamic radius R in isopropanol was... h It is 13.5nm.

[0064] Preparation of dispersant A5 - tert-butyl methacrylate, polyethylene glycol methacrylate

[0065] 2.0 g of tert-butyl methacrylate, 3.0 g of polyethylene glycol methacrylate (degree of polymerization 10, molecular weight approximately 500), and 5.0 g of isopropanol were added to a three-necked flask purged with nitrogen. The mixture was stirred and heated to 90 °C. After the temperature stabilized, 0.30 g of dimethyl azobisisobutyrate was added. The mixture was heated and stirred for 8 hours until the monomer and initiator were completely converted (conversion rate greater than 99%). 85 g of pure water was added and stirred until completely dissolved. After cooling and standing to room temperature, a solution containing the surfactant was obtained. The surfactant had Mn = 62300, PDI = 1.83, formed micelles with a diameter of 10.9 nm in water, and a hydrodynamic radius R in isopropanol. h It is 15.9nm.

[0066] Preparation of dispersant A6 - phenyl methacrylate, polyethylene glycol methyl ether methacrylate

[0067] Phenyl methacrylate (4.0 g), polyethylene glycol methyl ether methacrylate (degree of polymerization 20, molecular weight approximately 950, 6.0 g), and isopropanol (5.0 g) were added to a three-necked flask purged with nitrogen. The mixture was stirred and heated to 90°C. After the temperature stabilized, dimethyl azobisisobutyrate (0.60 g) was added, and the mixture was heated and stirred for 8 hours until the monomer and initiator were completely converted (conversion rate greater than 99%). Pure water (85 g) was added and stirred until completely dissolved. After cooling to room temperature, a solution containing the surfactant was obtained. The surfactant had Mn = 46800, PDI = 1.88, formed micelles with a diameter of 14.2 nm in water, and a hydrodynamic radius R in isopropanol. h It is 12.3nm.

[0068] Example 1

[0069] A 3L ball mill jar was filled with 50g (10% wt) of dispersant A1 aqueous solution, 50g of SuperP, 1kg of water, and 5kg of zirconia grinding column. After sealing the jar, the mixture was milled for 24 hours at 250 rpm using a horizontal ball mill. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 1034 nm using a nanoparticle size analyzer, and the dispersion viscosity was 34 mPa·s. -1 The time it took for the foam to disappear was recorded as two days.

[0070] Example 2

[0071] A 3L ball mill jar was filled with 50g (10% wt) of dispersant A2 aqueous solution, 50g of SuperP, 1kg of water, and 5kg of zirconia grinding column. After sealing the jar, the mixture was ground for 24 hours using a horizontal ball mill at 250 rpm. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 1334 nm using a nanoparticle size analyzer, and the dispersion viscosity was 45 mPa·s. -1 The time it took for the foam to disappear was recorded as two days.

[0072] Example 3

[0073] 50 g of dispersant A3 aqueous solution (10% wt), 50 g of SuperP, 1 kg of water, and 5 kg of zirconia grinding column were added to a 3 L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 878 nm using a nanoparticle size analyzer, and the viscosity of the dispersion was 26 mPa·s. -1 The time it takes for the bubbles to disappear is recorded as one day.

[0074] Example 4

[0075] 50 g of dispersant A4 aqueous solution (10% wt), 50 g of SuperP, 1 kg of water, and 5 kg of zirconia grinding column were added to a 3 L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 1260 nm using a nanoparticle size analyzer, and the viscosity of the dispersion was 38 mPa·s. -1 The time it took for the foam to disappear was recorded as two days.

[0076] Example 5

[0077] 50 g of dispersant A5 aqueous solution (10% wt), 50 g of SuperP, 1 kg of water, and 5 kg of zirconia grinding column were added to a 3 L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 1139 nm using a nanoparticle size analyzer, and the viscosity of the dispersion was 32 mPa·s. -1 The time it took for the foam to disappear was recorded as two days.

[0078] Example 6

[0079] A 3L ball mill jar was filled with 50g (10% wt) of dispersant A6 aqueous solution, 50g of SuperP, 1kg of water, and 5kg of zirconia grinding column. After sealing the jar, the mixture was milled for 24 hours at 250 rpm using a horizontal ball mill. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 1227 nm using a nanoparticle size analyzer, and the dispersion viscosity was 36 mPa·s. -1 The time it took for the foam to disappear was recorded as two days.

[0080] Example 7

[0081] A 3L ball mill jar was filled with 30g (10% wt) of dispersant A3 aqueous solution, 50g of SuperP, 1kg of water, and 5kg of zirconia grinding column. After sealing the jar, the mixture was milled for 24 hours at 250 rpm using a horizontal ball mill. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 3673 nm using a nanoparticle size analyzer, and the dispersion viscosity was 226 mPa·s. -1 And record the time it takes for the foam to disappear that is more than two days.

[0082] Example 8

[0083] 100 g (10% wt) of dispersant A3 aqueous solution, 50 g of SuperP, 1 kg of water, and 5 kg of zirconia grinding column were added to a 3 L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 646 nm using a nanoparticle size analyzer, and the viscosity of the dispersion was 21 mPa·s. -1 And record the time it takes for the foam to disappear that is more than two days.

[0084] Example 9

[0085] 100 g (10% wt) of dispersant A3 aqueous solution, 100 g of SuperP, 1 kg of water, and 5 kg of zirconia grinding column were added to a 3 L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 2297 nm using a nanoparticle size analyzer, and the viscosity of the dispersion was 130 mPa·s. -1 And record the time it takes for the foam to disappear that is more than two days.

[0086] Example 10

[0087] Add dispersant A3 aqueous solution (30g, 10% wt), TERGITOL TM XD(1g), 31R1 (1g), SuperP (50g), water (1kg), and a zirconia grinding column (5kg) were added to a 3L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 366 nm using a nanoparticle size analyzer, and the dispersion viscosity was 11 mPa·s. -1 The time it took for the foam to disappear was recorded as three hours.

[0088] Comparative Example 1

[0089] Briji98 dispersant (5g), SuperP (50g), water (1kg), and a zirconia grinding column (5kg) were added to a 3L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was measured to be 1693 nm using a nanoparticle size analyzer, and the dispersion viscosity was 72 mPa·s. -1 And record the time it takes for the foam to disappear that is more than two days.

[0090] Comparative Example 2

[0091] dispersant TERGITOL TM XD (5g), SuperP (50g), water (1kg), and a zirconia grinding column (5kg) were added to a 3L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was undetectable using a nanoparticle size analyzer, and the viscosity of the dispersion was 420 mPa·s. -1 And record the time it takes for the foam to disappear that is more than two days.

[0092] Comparative Example 3

[0093] dispersant 31R1 (5g), SuperP (50g), water (1kg), and a zirconia grinding column (5kg) were added to a 3L ball mill jar. After sealing the jar, the mixture was ground in a horizontal ball mill at 250 rpm for 24 hours. The carbon black aqueous dispersion was obtained by filtering the grinding column through a 50-mesh sieve. The average particle size was undetectable using a nanoparticle size analyzer, and the dispersion viscosity was 629 mPa·s. -1 And record the time it takes for the foam to disappear that is more than two days.

[0094] Table 1 Performance data of the embodiments and comparative examples

[0095]

Claims

1. An aqueous dispersion of a carbon-based material, comprising a carbon-based material and a dispersant, characterized in that: The dispersant is a multiblock copolymer of formula (1). Among them, R 1 R 4 It is independently selected from hydrogen, C1-C5 straight-chain or branched alkyl, or C1-C5 straight-chain or branched alkyl ether; R 2 R 5 Independently selected from oxygen, imino, C1-C9 straight-chain or branched or cyclic alkyl imino, C1-C9 aryl imino; R 3 Selected from phenyl, C1-C4 straight-chain or branched alkyl groups; R 6 Selected from polyethylene glycol derivatives (CH2CH2O) q Z, where q is an integer greater than 9 and less than or equal to 100, and Z is selected from hydrogen, C1-C3 straight-chain or branched alkyl groups.

2. The aqueous dispersion of carbon-based material according to claim 1, characterized in that: in R 1 R 4 Independently selected from hydrogen and methyl; R 2 R 5 Independently selected from oxygen and imino groups; R 3 Selected from phenyl, C1-C4 straight-chain or branched alkyl groups; R 6 Selected from polyethylene glycol derivatives (CH2CH2O) q Z, where q is an integer greater than 9 and less than or equal to 100, and Z is selected from hydrogen, C1-C3 straight-chain or branched alkyl groups.

3. The aqueous dispersion of carbon-based material according to claim 2, characterized in that: in R 1 R 4 Independently selected from methyl; R 2 R 5 Independently selected from oxygen; R 3 Selected from phenyl, methyl, and tert-butyl; R 6 Selected from polyethylene glycol derivatives (CH2CH2O) q Z, where q is an integer greater than 9 and less than or equal to 50, and Z is selected from hydrogen, C1-C3 straight-chain or branched alkyl groups.

4. The aqueous dispersion of carbon-based materials according to any one of claims 1 to 3, characterized in that: The dispersant satisfies at least one of conditions (I) to (III): (I)x+y=1, and x / y=1~9, (II) The HLB value of the dispersant is 8 to 14. (III) The micelles formed by the dispersant in water have a micelle size of 5 to 30 nm.

5. The aqueous dispersion of carbon-based material according to claim 4, characterized in that: The dispersant is a multiblock copolymer with more than 5 blocks, and the block length of a single block is 1 to 10.

6. The aqueous dispersion of carbon-based material according to claim 1, characterized in that: The number average molecular weight of the dispersant is 5,000 to 100,000.

7. The aqueous dispersion of carbon-based material according to claim 1, characterized in that: The average particle size of the aqueous dispersion of the carbon-based material is 200–5000 nm.

8. The aqueous dispersion of carbon-based material according to claim 7, characterized in that: The specific surface area of ​​the carbon-based material is 10 to 1000 m². 2 / g, wherein the carbon-based material is selected from at least one of superconducting carbon, carbon black SP, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, superconducting celestial black, graphite, artificial graphite, carbon, carbon black, activated carbon, acetylene black, phenolic resin, asphalt, tar, and carbon fiber.

9. The aqueous dispersion of carbon-based material according to claim 8, characterized in that: The carbon-based material is carbon black SP, and the average particle size of the aqueous dispersion of the carbon-based material is 400-3000 nm.

10. The aqueous dispersion of carbon-based material according to claim 1, characterized in that: The dispersant accounts for 5% to 10% of the total mass of the aqueous dispersion of the carbon-based material.

11. The aqueous dispersion of carbon-based material according to claim 1, characterized in that: The aqueous dispersion of the carbon-based material contains one or more additives selected from the group consisting of: defoamers, thickeners, rheology modifiers, and wetting agents.

12. The application of an aqueous dispersion of a carbon-based material according to any one of claims 1-11, characterized in that: The aqueous dispersion of the carbon-based material is used as a conductive agent in the preparation of PVDF conductive binder.

Citation Information

Patent Citations

  • Conductive paste and mixture paste for lithium ion battery positive electrode

    CN107528067A

  • Negative electrode composite conductive agent and preparation method thereof, lithium ion battery containing negative electrode composite conductive agent and preparation method of lithium ion battery

    CN111916743A

  • Polymer, conductive paste, positive electrode sheet, secondary battery, and electric device

    CN115340624A

  • Graphene composite conductive agent, preparation method and application

    CN115621463A

  • Binder compound, conductive binder, and secondary battery comprising same

    WO2023044754A1